BUDAYA KERJA APARATUR SIPIL NEGARA PADA MASA PANDEMI COVID-19 DI DINAS KEPENDUDUKAN DAN CATATAN SIPIL KABUPATEN MINAHASA TENGGARA - Wuri, Christine D. D.; Tasik, Femmy C. M.; Goni, Shirley Y. V. I. (AGRI-SOSIOEKONOMI, 2022)
This study aims to analyze how the work culture of the state civil apparatus during the covid-19 pandemic was at the Department of Population and Civil Registration of Southeast Minahasa Regency. This study uses a qualitative descriptive method with research indicators consisting of habits, rules and values of the point of data analysis used, which consists of data reduction, data presentation and data verification. The results showed that the work culture of state civil servants at the Population and Civil Registration Service of Southeast Minahasa Regency in carrying out work showed that work habits as a work culture during the COVID-19 pandemic were carried out in accordance with established regulations, namely employees can carry out work through working in office, work at home and can work anywhere in accordance with the implementation instructions or implementation guidelines set by the government. If public services are carried out at the office, the community and officers must follow the health protocols that have been set in an effort to prevent the spread of COVID-19. Meanwhile, for those who do work from home or from anywhere who are tasked with serving public public services, this is done through the use of applications that have been provided by the service.